Efektifitas Model Numbered Heads Together Terhadap Keaktifan Belajar Pendidikan Pancasila Dan Kewarganegaraan - Nasrul Latifah; Risti Aulia Ulfah (Universitas Muhammadiyah Magelang, 2026)
Pancasila and Citizenship Education (PPKn) specifically aims to develop active and responsible citizens. Although the Pancasila and Citizenship Education (PPKn) subject is designed to develop active and responsible citizens, the reality in class III MI Ma'arif Setono shows that the level of student learning activity is not optimal. This study aims to determine the effectiveness of the Numbered Heads Together model to increase student learning activity in PPKn subjects in class III MI Setono. This type of research is a quasi-experimental, with a pretest-posttest control group design. The research sample is class III Ar-Rahman (experimental class) and class III Al-Malik (control class). Data collection instruments use questionnaires and observations. The results of the analysis show that the Numbered Heads Together model has been proven to be effective in increasing student learning activity in the PPKn subject in class III MI Setono. This is proven based on the t-test analysis obtained a significance value of 0.000 < 0.005. The Numbered Heads Together model has been proven to be effective in increasing student learning activity in the PPKn subject in class III MI Setono as evidenced by the N-gain value of 64.96%.